Preliminary Phytochemical Screening, Antibacterial and Antifungal Activity of Artemisia Vulgaris - Mainali, Teeka Ram (Shaheed Smriti Journal, 2024)
Artemisia vulgaris (L), commonly known as “mugwort”, is a species of flowering plant in the daisy family Asteraceae, a species with great importance in the history of medicine and was called the “mother of herbs” in the Middle Ages. It is a common herbaceous plant that exhibits high morphological and phytochemical variability depending on the location where it occurs. This species is well known almost all over the world. It is a very important medicinal plant or herb which is used widely for the treatment of various ailments traditionally. The present study of leaves of Artemisia vulgaris was examined for their phytochemical screening, antibacterial and antifungal activity against different pathogenic micro-organisms Staphylococcus aureus, E. coli and Candida. Phytochemical analysis of the methanolic extracts showed the presence of various phytoconstituents like glycosides, flavonoids, saponins, proteins, triterpenoids, tannins and alkaloids. A total of 3 microorganisms were used to find out the antibacterial and antifungal activity of the plant extract. The methanol extract of plant showed strong antibacterial activity against Staphylococcus aureus and E. coli with zones of inhibition of 14 mm and 6 mm respectively. Similarly, the extract showed relatively weak antifungal activity against Candida with zones of inhibition of 12 mm. This finding concludes that the methanol extract has strong antibacterial activity and could be responsible for the presence of active compounds like flavonoids, tannins, saponins, alkaloids, and proteins. A further study should be done to investigate more active compounds of Artemisia vulgaris L, which can be beneficial for the pharmacology field.